Communication Technology: Rebuilding a Better Global Civilization on Earth - Sirken, Faustinus (Jurnal Sosial Humaniora, 2025)
The evolution of communication technology fuels ongoing introspection among humans, shaping their self-perception and worldview. As reliance on these tools deepens, individuals delve into their existence and the societal constructs that govern their lives, potentially steering the development of communication tech for global betterment. Historically, humans have pondered their role as sources of authority and meaning. Liberal perspectives frame humans as subjective authorities, emphasizing internal experiences to inspire universal meaning. In contrast, Dataists view humans as sources of authority and meaning within collective narratives, highlighting the richness of intersubjective experiences among many individuals in one world. Utilizing advanced communication technology, notably computer algorithms, to interpret collective human narratives, this paper suggests a pathway for enhancing global civilization. It advocates harnessing technology, specifically algorithmic intelligence, to restore a cohesive global identity founded on principles of freedom and equality. Employing phenomenological methods, this research examines human experiences within the realm of communication technology, drawing on humanism, subjectivism, intersubjectivism, and dataism as theoretical frameworks.